Philosophical analysis of critical pedagogy as a basis for developing a comprehensive teacher education program - Abestano, Recolito C.
This study is a conceptual analysis of Critical Pedagogy (CP). CP provides a means of combining critique of educational procedures with a thorough analysis of educational ideals, goals, and objectives based on a solid trust in individual teachers’ transforming capacity (Giroux, 1985). As a pedagogy, CP assists teachers in making sense of the world of oppression and dominance as they struggle to create a more just, democratic, and egalitarian society (Kitchenloe, 2007). This thesis is aimed at developing a philosophical framework for understanding and implementing CP. Soltis’s analytic methods, namely, the generic-type, differentiation-type, and condition-type, were employed to answer the concerns of this study. Relevant examples, definitions, and classroom practices of CP were presented to carry out this research. The procedures consist of generic-type, differentiation-type, and condition-type analysis to determine the distinctive features of the concept of CP and to ascertain the correct linguistic use of the term “CP”. The analyses that were carried out also covered the fundamental concerns of CP, such as its goals, working principles, and instances. The analytic approach of this study was further used to articulate CP’s supposed content, learning objectives, methodology, and goals, when deployed in classroom learning. The analyses in this research yielded results that served as the basis for developing a philosophical framework for a teacher education program whose operations are determined by the philosophy of CP.